INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON CONSUMERS AWARENESS, ATTITUDE, ATTRIBUTION AND PURCHASE DECISION WITH FMCG PRODUCTS - Subbusundaram, Hashnee; Radha, K.V. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Societal assumptions about CSR have developedamid the recent decades thus have organizations commitments to CSR. These desires on one hand and responsibilities on the other hand, are having now a recognizable impact on the marketplace for goods and services. A study from surveys that many consumers care about the ethical performance of a business. A large proportion of customers say that they care regards manufacturing standards, and there's alternative confirmation that consumers are increasingly keen on CSR and problems with socially capable production, just about characterised as practices of production that respect individuals, communities and the environment. The current study is an endeavour to grasp CSR from consumer Behaviour perspective. This study expects to, measure the knowledge/ awareness level of customers ‘regarding CSR activities of elite corporations, to know customers ‘attitude towards getting from corporations that practise CSR, perceive customers' attributions regarding the company’s motives behind CSR and therefore the impact of CSR on consumers ‘buying decisions. This analysis can facilitate marketing managers, who are taking under consideration corporate social commitment as a lot of strategic way to profit community furthermore as their business.